Effects of the work limitations on the career path of a cohort of health workers - Talini, Donatella; Romeo, Gianpaolo; Baldasseroni, Alberto; Mignani, Aldo; Cristaudo, Alfonso (La Medicina del Lavoro, 2017)
Background: The median age of the workforce, and of healthcare workers in particular, is increasing, resulting in a reduced work capacity. This may prompt the occupational physician to issue fitness for work limitations. Objectives: To examine the health surveillance data collected over 20 years on the employees of a large healthcare institution to identify the effects of the limitations imposed on their career paths. Methods: The database of health surveillance records gathered over the years was analysed using the same dedicated software. Fourteen types of limitations were classified via a “text mining” treatment. 3,653 subjects were selected, divided in two groups (A: with a limitation and B: without limitation) comprised of 655 and 2,998 subjects, respectively. The subjects were then ranked on the basis of departments and tasks involved. We also evaluated the number of departmental changes for each worker and the corresponding rate of change for the three groups A, B and B post-limitation. Results: Limitations have been increasing in parallel with the aging of workers, in particular those relating to Manual Load Handling/Posture (MLH/P). The limitations due to Allergy/Latex lasted longer, and in a greater proportion than MLH/P, particularly when compared to the limitation for Shift Work and those for “Other Limitations” that were shrinking faster. Conclusions: There is a clear relationship between certain types of limitations/prescriptions and workers’ ages. It is necessary to carry out an assessment of the association with the work performed in order to implement age management strategies aimed at maintaining work capacity in aging workers.